National Security:Countering Pandemics and the Threats of Bioterrorism - Nabipour, Pourya (National Interest, 2021)
This paper highlights the security threats like COVID-19 as non-traditional threats and explains how COVID-19 and experiences from bio-terrorism remain a likely threat and how it poses tangible tests to the national security, including the public health system. This research paper argues that the COVID-19 revealed that the security threats of the 21 century need multidisciplinary knowledge of national security beyond the state-centric approaches that cover many fields, and shows greater international cooperation, and more multilateralism. The paper also argues that to strengthen global health security, there is a need for collaboration and commitment across disciplines and sectors. Furthermore, new attitudes, approaches, and methodologies are required to ensure national security in the modern era where threats are rapidly developing. National security cannot be ensured through traditional methods and approaches anymore and require the recalibration of existing doctrines, concepts and strategies on national security, legal and their adaptation to the modern conditions.